Comparison between Two Different Deployment Types of Road-Side Devices Reducing Incident-Related Potential Conflicts - Jaehyeong Lee; Jin-Tae Kim (Engineering Proceedings, 2023)
The carpet-Type materials painted yellow in pedestrian waiting areas are safety devices used to prevent collisions with vehicles and children. They are primarily recommended to be placed on both the pavement and the wall sides, but local governments in the Republic of Korea place them only on the pavement side, excluding the wall part to reduce the deployment costs and increase the number of deployment sites. The difference in effectiveness between these Types may be different, but this has not yet been proven. This study examines the difference between these Types found in the field test. The test employed two different measures: (1) the level of driver visibility and (2) the vehicle deceleration rate. As a result of the analysis, the yellow carpet installed on both the pavement and the wall sides was comparatively more effective. The test results suggest that this yellow carpet Type should be installed on both pavement and wall sides, particularly for school zone areas, to maximize its safety effects.